ChemInform Abstract: Synthesis and Characterization of Ammonium‐, Pyridinium‐, and Pyrrolidinium‐Based Sulfonamido Functionalized Ionic Liquids. Issue 5 (13th February 2013) - Saravanamurugan, Shunmugavel; Fehrmann, Rasmus; Riisager, Anders
Abstract New ionic liquids (I)—(IV) are synthesized and their thermal characteristics are evaluated by DSC and thermogravimetric analysis.